1993
DOI: 10.1016/0035-9203(93)90077-4
|View full text |Cite
|
Sign up to set email alerts
|

Filovirus activity among selected ethnic groups inhabiting the tropical forest of equatorial Africa

Abstract: Seroepidemiological surveys were conducted to determine the frequency and distribution of filovirus activity among selected ethnic groups inhabiting the tropical forests of the Central African Republic. 427 serum specimens were collected from hunter-gatherers and subsistence farmers living in forest environs in the Lobaye District south of the river Lobaye and west of the river Oubangui. Striking serological evidence for filovirus activity was found in both populations. Ebola virus appears to be the most activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
19
3
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 8 publications
9
19
3
1
Order By: Relevance
“…These results are consistent with previous studies showing seroprevalence rates ranging from 1.8% to 21.3% [30][34]. However, these latter surveys used a poorly specific IFAT method associated with frequent false-positive results [27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with previous studies showing seroprevalence rates ranging from 1.8% to 21.3% [30][34]. However, these latter surveys used a poorly specific IFAT method associated with frequent false-positive results [27].…”
Section: Discussionsupporting
confidence: 93%
“…Likewise, a seroprevalence of 13.2% was found in the Aka Pygmy population of Central African Republic, where no ZEBOV outbreaks have ever been reported [29]. These findings confirmed those of older studies based on less-specific immunofluorescence assays that showed an antibody prevalence of around 10% in several non epidemic parts of Africa [30][34]. In contrast, a more recent survey showed a low anti-ZEBOV IgG prevalence (1.4%) among 979 people living in the northern region of Gabon that experienced EHF outbreaks between 1994 and 1997 [35].…”
Section: Introductionsupporting
confidence: 84%
“…The Ebola virus is endemic to central Africa, [6][7][8][9][10][11] occurring in isolated epidemics throughout the region, [12][13][14] specifically on three occasions between 1994 and 1996 in Gabon. 15,16 Several strains of the virus have been characterized, some of which may cause a clinically atypical disease in an as yet unknown proportion of cases.…”
mentioning
confidence: 99%
“…Neben dem Verwerten von Wildtierkadavern und dem Konsum von rohem beziehungsweise nicht durchgebratenem Fleisch, gilt ganz allgemein der direkte Kontakt zu Wildtieren (inklusive Chiroptera), besonders für das EBV, als Risikofaktor [20,52,59,73,80,86].…”
Section: Ebolavirus -Risiko Jagd Und Wildtierkadaverunclassified